Clinical retrospective analysis of 218 cases of infectious endophthalmitis - Chunhui Li; Zheyi Yan; Guohong Zhou; Yan Gao; Peini Cheng (BMC Ophthalmology)
Abstract Purpose Endophthalmitis is a serious medical condition that needs immediate antibiotic therapy. There are few studies analyzing the pathogenic bacteria of endophthalmitis in China recently. This study was conducted to analyze the pathogenic factors, pathogenic bacteria and prognosis of infectious endophthalmitis. Methods A cross-sectional study was conducted from January 2016 to December 2020 in Shanxi Eye Hospital. Statistical analysis by using Logistic regression analysis were performed to evaluate of independent risk factor for prognostic factors for poor visual acuity. Results Positive case of specimen culture was detected in 96 cases, accounting for 44.04%. Staphylococcus epidermidis, the most common bacteria, accounted for 32.98% (31/94), mainly in traumatic endophthalmitis and postoperative endophthalmitis, and was extremely sensitive to vancomycin (96.77%). The Gram-positive bacteria were highly sensitive to vancomycin (87.01%) and relatively sensitive to levofloxacin (68.83%). Gram-negative bacteria were highly sensitive to levofloxacin (88.24%). 12.39% of patients with visual acuity > 0.02 at admission and 27.98% at discharge, the difference was statistically significant (χ 2  = 17.449, P < 0.001). Logistic regression analysis of traumatic endophthalmitis group showed that intraocular foreign body was an independent risk factor for poor visual acuity after post-operation (OR = 2.215. P = 0.016). Conclusions As society progresses and hygiene concepts increase in China, the bacteria that cause infection are changing, and factors that influence prognosis may also be changing. Clarifying the different causative factors and etiological characteristics of infectious endophthalmitis are important to provide appropriate clinical treatment.